1976
DOI: 10.1111/j.1465-7295.1976.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Control and Risk

Abstract: Previous empirical research examining the link between firm risk and the type of stockholder control has yielded conflicting results. These studies have sorted firms into two categories, owner‐controlled firms and manager‐controlled firms, even though the theoretical discussion implies behavior associated with three distinct groups. This paper argues both theoretically and empirically that an owner‐manager has more incentive and more opportunity to take risks than a hired manager. Moreover, a hired manager und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
(2 reference statements)
0
12
0
2
Order By: Relevance
“…This could be probably one of the reasons for a slower growth than if they sought to maximize profi ts. McEachern (1976), too, found that there is more market-related risk in the owner-managed fi rms. Stano (1976) has a different view, according to which, since management-controlled fi rms are more leveraged and the rate of return is highly volatile, growth rate is low and performance is poor.…”
Section: The Relation Between Ownership and Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…This could be probably one of the reasons for a slower growth than if they sought to maximize profi ts. McEachern (1976), too, found that there is more market-related risk in the owner-managed fi rms. Stano (1976) has a different view, according to which, since management-controlled fi rms are more leveraged and the rate of return is highly volatile, growth rate is low and performance is poor.…”
Section: The Relation Between Ownership and Riskmentioning
confidence: 98%
“…Variations in profi tability are one of those measures which have been used by Cheng (2008) and Kakani et al (2001). McEachern (1976) used CAPM beta as their measure of risk. Many authors have applied methods using equity and market returns to calculate systematic and idiosyncratic risk.…”
Section: Riskmentioning
confidence: 99%
“…NOTES 1. Numerous studies have been conducted on the effect of the separation of ownership from control, with findings ranging from highly significant to no significant difference in corporate performance (Kamerschen, 1968;McEachern, 1975McEachern, , 1976; McKean and Kania, 1978;Palmer, 1973; Sorenson, 1974…”
Section: Grammentioning
confidence: 99%
“…Evidence from these studies ranges from findings of no significant difference in profit performance to significantly higher profit levels of owner‐controlled enterprises. Recent representative studies in this area include [17, 18, 23, 24, 25, 27, 28, 29].…”
Section: $10‐$25 $25‐$50 $50‐$100 $100‐$250 $250‐$500 Over $500 Totalmentioning
confidence: 99%
“…Evidence from these studies ranges from findings of no significant difference in profit performance to significantly higher profit levels of owner-controlled enterprises. Recent representative studies in this area include [17,18,23,24,25,27, 28,29]. 2 As of the end of 1978 stock SLAs accounted for approximately 17 percent of the total number of FSLIC-insured SLAs and 23 percent of total industry assets.…”
mentioning
confidence: 99%